If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6y + 5 = 0 Reorder the terms: 5 + 7x + 6y = 0 Solving 5 + 7x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 7x + -5 + 6y = 0 + -5 Reorder the terms: 5 + -5 + 7x + 6y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 7x + 6y = 0 + -5 7x + 6y = 0 + -5 Combine like terms: 0 + -5 = -5 7x + 6y = -5 Add '-6y' to each side of the equation. 7x + 6y + -6y = -5 + -6y Combine like terms: 6y + -6y = 0 7x + 0 = -5 + -6y 7x = -5 + -6y Divide each side by '7'. x = -0.7142857143 + -0.8571428571y Simplifying x = -0.7142857143 + -0.8571428571y
| -2x+7=5-(4x+7) | | -5a+6(a+2)=2(a+1)-3 | | 2x+2y=16 | | 8x-11=8(x-2) | | w^4-4=3 | | 2(3+5x)-5=61 | | 7(4+5x)+8= | | -(3+4p)+2p=-(5p+3) | | -4(7-6n)+2= | | 4(c+5)11c=110 | | .9(x+30)+.9x=108 | | -2(4-8b)=-3(1-7b) | | 96=-5x-5x+6 | | 4(2x-2)=24 | | (-3x-8)=(-7x-3) | | x-0.77777777777=1-7 | | -5(x-1)-x= | | -1-5x-3x=-1 | | 3y+19=4y+5 | | 1-x(x-3)=4x-1 | | 3x+0.375=4x-0.375 | | 3x+0.375=4-0.375 | | -112=-5x-7x+8 | | 6x+9=-57 | | 3x+x=144 | | -(x-4)-3=-4(x+8) | | 3x^2-125=0 | | 14*5-14=2*5+46 | | 7x+18.5x=64 | | -(-5+2r)+7r= | | -6x+2=-52 | | 12400+x+12400=22800 |